Replication of T4rII Bacteriophage in Escherichia coli K-12 (λ) - Buller, Clarence S. (1968)
The defect of T4rII replication in Escherichia coli K-12 (λ) can be phenotypically reversed by various supplements to the growth medium. Arginine, lysine, spermidine, and a number of diamines allowed varying levels of rII replication. The best reversion was obtained with 0.4 m sucrose in 0.002 to 0.005 m Ca(++). Monovalent cations severely inhibited reversion. A cell surface site of polyamine action is consistent with the fact that spermidine inhibits phage ghost-induced cell lysis and with the finding that sufficient polyamine is available within the cells to allow normal patterns of neutralization of phage deoxyribonucleic acid, as detected by the polyamine content of progeny phage. In the absence of effective supplements, rII-infected cells swelled and lost refractility. The data indicate that a leaky cell envelop is involved. No difference in mucopeptides of uninfected K-12 (λ) and K-12 was detected and, because the mucopeptide in r(+) infected cells was found to be at least partially hydrolyzed midway through the lytic cycle, it did not appear that the rII defect concerned mucopeptide synthesis. The pattern of cell phospholipid synthesis changes after phage infection, but no difference was detected between r(+) and rII with regard to biosynthesis of phosphatidylethanolamine and phosphatidylglycerol.